Pembuatan Game Edukasi Bernarasi Sejarah Insiden Perobekkan Bendera Belanda Di Hotel Yamato Menggunakan Unity - Mochammad Yanuar Fitroni; Pratama Wirya Atmaja; Andreas Nugroho Sihananto (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The development of technology is increasingly advanced, there are many new innovations that are useful to facilitate activities, one of which is in the world of education. One of the innovations is an educational game that was created as a means of teaching and learning so that students and teachers can understand the material easily. The purpose of this research is to create a narrative game about one of the histories in Indonesia, where this educational game is a means of learning and to increase curiosity about the history of Indonesia. This educational game is made with a game engine called unity and the method used is interactive digital narratives (IDN) with several stages of development, namely requirements, general design, and detailed design. The result of this research is an educational game application narrating the history of the tearing of the Dutch flag at the Yamato Hotel and as a means of learning and introducing more history in Indonesia.